The Impact of Cloud Processing on the Ice Nucleation Abilities of Soot Particles at Cirrus Temperatures. Issue 3 (6th February 2020) - Mahrt, Fabian; Kilchhofer, Kevin; Marcolli, Claudia; Grönquist, Philippe; David, Robert O.; Rösch, Michael; Lohmann, Ulrike; Kanji, Zamin A.
Abstract: Soot particles are generally considered to be poor ice nucleating particles. Involvement of soot in clouds and their release back into the atmosphere can form residual particles with altered cloud forming potential. The impact and extent of such different cloud processing scenarios on ice nucleation is, however, not well understood. In this work, we present the impact of cloud processing of soot aerosols on subsequent ice nucleation cycles at T ≤233 K. Coupling of two continuous flow diffusion chambers allows the simulation of different cloud processing scenarios and investigation of subsequent ice nucleation activity of the processed particles. The processing scenarios presented here encompass contrail, cirrus, and mixed‐phase cloud processing, mimicking typical pathways that soot particles can be exposed to in the atmosphere. For all scenarios tested, the processed particles showed an enhanced ice active fraction for T <233 K. The relative humidity with respect to water for the ice nucleation onset was observed to be on average approximately 10% (relative humidity with respect to ice, R H i ≈16%) lower for the cloud‐processed particles compared to the unprocessed soot for which ice nucleation was observed close to or at homogeneous freezing conditions of solution droplets. We attribute the enhanced ice nucleation abilities of the cloud‐processed soot to a pore condensation and freezing mechanism and have identified key parameters governing these changes. Enhanced ice nucleation abilities of soot in cirrus clouds can have significant impacts, given the importance of the atmospheric ice phase for precipitation formation and global climate. Key Points: Ice nucleation onto soot particles is significantly enhanced by cloud processing Enhanced ice nucleation activity is not due to preactivation from ice preserved in pores, instead results from morphology change favoring pore condensation and freezing Hydrometeor formation on soot particles during processing cycle is key for enhanced ice nucleation activity